Simultaneous optimization of fixture and cutting parameters of thin-walled workpieces based on particle swarm optimization algorithm. (January 2018) - Wang, Shasha; Jia, Zhenyuan; Lu, Xiaohong; Zhang, Haixing; Zhang, Chi; Liang, Steven Y
The elastic deformation of thin-walled workpieces is because of the combination effect of cutting force and clamping force, which also leads to processing error. Clamping force and cutting force have coupling effect during this process. Clamping force and cutting force are mainly influenced by fixture, and cutting parameters, respectively. Instead of considering coupling effect of clamping force and cutting force when optimizing fixture and cutting parameters step by step, this paper establishes a recursive optimizing model through particle swarm optimization (PSO) and finite element (FE) methods to optimize fixture and cutting parameters simultaneously. With the guidance of PSO under certain deformation conditions, FE analysis finds optimal combinations of fixture and cutting parameters, which reduce elastic deformation of thin-walled workpieces. The case study shows that the model had achieved optimization results. It effectively reduced elastic deformation of thin-walled workpieces during processing and improved the machining accuracy.